Manajemen Daftar Pemilih Dalam Penyelenggaraan Pemilihan Umum Legislatif Di Provinsi Sulawesi Utara Tahun 2014 - Golonggom, Zulkifli; Liando, Daud; Mamentu, Michael (JURNAL ILMIAH SOCIETY, 2016)
Updating the data of voters and the establishment of the voter list, which is part of the implementation phase general election until today is still a national political issue quite seriously. This study was conducted to analyze and reveal the causes of voter lists have not been as good management that is focused on the organization of legislative elections in the province of North Sulawesi. From this research it was found that the management of voter lists in the organization of legislative elections in North Sulawesi province in 2014 have not been going well since the function of planning, organizing, and monitoring have not been fully applied in the management of the voter list. By it necessary to make improvements in the management of voter lists in planning data collection, establishment Updating Voter Data Officer, the District Selection Committee and the Voting Committee, the operational budget adjustments in the data collection stage, maximizing the internal oversight functions. Keywords: Management, Voter Registration, Legislative Election.